Mucosal multivalent NDV-based vaccine provides cross-reactive immune responses against SARS-CoV-2 variants in animal models - González-Domínguez, Irene; Abdeljawad, Adam; Lai, Tsoi Ying; Boza, Marta; McCroskery, Stephen; Lemus, Nicholas; Slamanig, Stefan; Singh, Gagandeep; Warang, Prajakta; Yellin, Temima; Abbad, Anass; Carreño, Juan Manuel; et al. (Frontiers in Immunology, 2025)
IntroductionA new generation of mucosal vaccine against the ever-evolving SARS-CoV-2 is of great value to fight COVID-19. In previous studies, our groups developed a viral vector vaccine based on an avirulent Newcastle disease virus (NDV) expressing the prefusion-stabilized spike protein of SARS-CoV-2 (NDV-HXP-S).MethodsHere we characterized the in vivo biodistribution and immunogenicity of a live mucosal NDV-HXP-S vaccine in animal models.ResultsNDV showed restricted replication in mice and hamsters. Despite limited replication, intranasal live NDV-HXP-S provided protection against SARS-CoV-2 challenge and direct-contact transmission in hamsters. Importantly, a trivalent live NDV-HXP-S vaccine (Wuhan, Beta, Delta) induced more cross-reactive antibody responses against the phylogenetically distant Omicron variant than the ancestral vaccine. Furthermore, intranasal trivalent live NDV-HXP-S boosted systemic and mucosal immunity in mice pre-immunized with mRNA vaccine.DiscussionOverall, a mucosal multivalent live NDV-HXP-S vaccine shows great promise as a safe, next-generation vaccine conferring broad mucosal and systemic immunity against future SARS-CoV-2 variants.